Answer:
C) abH
Step-by-step explanation:
a × b × H
= abH
The answer is option C
Answer:
2550/6= 425
he has to save 425 each month
Step-by-step explanation:
Answer:
Part 1) ![P=(4x+4)\ units](https://tex.z-dn.net/?f=P%3D%284x%2B4%29%5C%20units)
Part 2)
a) ![P=32\ units](https://tex.z-dn.net/?f=P%3D32%5C%20units)
b) ![P=26\ units](https://tex.z-dn.net/?f=P%3D26%5C%20units)
c) ![P=13\frac{1}{3}\ units](https://tex.z-dn.net/?f=P%3D13%5Cfrac%7B1%7D%7B3%7D%5C%20units)
Step-by-step explanation:
<u><em>The complete question in the attached figure</em></u>
Part 1) Write an expression for the perimeter of the shape
we know that
The figure is composed by a larger square, a rectangle and a smaller square
1) The area of the larger square is given
![A=x^2\ units^2](https://tex.z-dn.net/?f=A%3Dx%5E2%5C%20units%5E2)
so
The length and the width of the larger square is x units
2) The area of the rectangle is given
![A=x\ units^2](https://tex.z-dn.net/?f=A%3Dx%5C%20units%5E2)
so
The length of the rectangle is x units and the width is 1 unit
3) The length and the width of the smaller square is x units
see the attached figure N 2 to better understand the problem
Find out the perimeter
The perimeter is the sum of all the sides.
so
![P=(x+x+x+x+1+1+1+1)](https://tex.z-dn.net/?f=P%3D%28x%2Bx%2Bx%2Bx%2B1%2B1%2B1%2B1%29)
![P=(4x+4)\ units](https://tex.z-dn.net/?f=P%3D%284x%2B4%29%5C%20units)
Part 2) Find the perimeter for each of the given values of x.
a) For x=7 units
Substitute the value of x in the expression of the perimeter
![P=(4(7)+4)=32\ units](https://tex.z-dn.net/?f=P%3D%284%287%29%2B4%29%3D32%5C%20units)
b) For x=5.5 units
Substitute the value of x in the expression of the perimeter
![P=(4(5.5)+4)=26\ units](https://tex.z-dn.net/?f=P%3D%284%285.5%29%2B4%29%3D26%5C%20units)
b) For x=7/3 units
Substitute the value of x in the expression of the perimeter
![P=(4(\frac{7}{3})+4)=\frac{40}{3}=13\frac{1}{3}\ units](https://tex.z-dn.net/?f=P%3D%284%28%5Cfrac%7B7%7D%7B3%7D%29%2B4%29%3D%5Cfrac%7B40%7D%7B3%7D%3D13%5Cfrac%7B1%7D%7B3%7D%5C%20units)
No, John is incorrect.
<h3>
Correct work shown:</h3>
![\sf x^2 - 6x - 7 = 0](https://tex.z-dn.net/?f=%5Csf%20x%5E2%20-%206x%20-%207%20%3D%200)
![\sf x^2 - 6x = 7](https://tex.z-dn.net/?f=%5Csf%20x%5E2%20-%206x%20%3D%207)
![\sf x^2 - 6x + 9= 7 + 9](https://tex.z-dn.net/?f=%5Csf%20x%5E2%20-%206x%20%20%2B%209%3D%207%20%2B%209)
![\sf (x-3)^2= 16](https://tex.z-dn.net/?f=%5Csf%20%28x-3%29%5E2%3D%2016)
![\sf x-3=\pm \sqrt{16}](https://tex.z-dn.net/?f=%5Csf%20x-3%3D%5Cpm%20%5Csqrt%7B16%7D)
![\sf x-3= \pm 4](https://tex.z-dn.net/?f=%5Csf%20x-3%3D%20%5Cpm%204)
![\sf x= + 4 + 3 \quad or \quad x = -4 + 3](https://tex.z-dn.net/?f=%5Csf%20x%3D%20%2B%204%20%2B%203%20%5Cquad%20or%20%5Cquad%20x%20%3D%20-4%20%2B%203)
![\sf x= 7 \quad or \quad x = -1](https://tex.z-dn.net/?f=%5Csf%20x%3D%207%20%5Cquad%20or%20%5Cquad%20x%20%3D%20-1)
The correct answer should be x = 7 or x = -1
Sum of the first two is:
-3x+5+7-4x = -7x+12
That subtracted from 5x+17:
5x+17-(-7x+12) = 12x+5